Implementasi Pendidikan Moderasi Beragama di Kabupaten Sintang Provinsi Kalimanatan Barat - Faisal, Muhammad (Attractive : Innovative Education Journal, 2024)
This research aims to analyze the implementation of religious moderation education and the description of religious moderation in Sintang Regency, West Kalimanatan Province. This type of research is qualitative research with a philosophical, sociological, theological and juridical approach. The informants in this research consisted of; Chairman of the Mosque/FKUB, Chairman of DMI, Head of the Ministry of Religion Office and Chairman of the Cathedral. Furthermore, the data collection methods used were observation, interviews, documentation and reference tracking. Meanwhile, data processing and analysis techniques are carried out by means of data reduction, data presentation, and drawing conclusions. The results of this research showed that the implementation of religious moderation education in Sintang Regency first needed socialization conveyed through an interview with the Head of the Ministry of Religion when giving directions and opening the Religious Moderation Strengthening Training in Sintang Regency, Sintang Regent's Praja Office. Furthermore, the Head of the Ministry of Religion emphasized that solving problems through dialogue is a sign of being a civilized nation. Description of the life of the Religious Moderation Society in Sintang Regency. Based on the results of interviews with Mr. H. Anang Nurkholis who serves as chairman of the Great An-Nur Sintang Mosque, as well as the administrator of the FKUB of Sintang Regency, information was obtained that religious moderation means that we place religion in a moderate (middle) way. , not being panicked, and not taking sides, meaning we remain in the middle position. Keywords: Religious Moderation Education, Implementing Religious Moderation Education